Penatalaksanaan Holistik Pada Pria Usia 85 Tahun Dengan Gout Arthritis Melalui Pendekatan Kedokteran Keluarga Di Puskesmas Rawat Inap Gedong Tataan - Chintya Chintya Redina Habsari; Fitria Saftarina (Medula, 2023)
Gout arthritis is a condition where there is an increase in serum uric acid levels above normal. Risk factors that influence high uric acid levels are age, genetics, excessive purine intake, obesity, and post menopause. This disease is important to be managed comprehensively because treatment goals can be achieved so that management needs to be carried out through a family approach. Identify internal and external risk factors and clinical problems present in the patient. Apply a holistic and comprehensive approach to family doctors according to the problems found in patients and carry out evidence-based medicine-based management that is family-approach, patient-centered and community-oriented. The study conducted is a Case Report. Primary data were obtained through history taking, physical examination through home visits and filling in the family folder, secondary data were obtained through patient medical record. Assessment is based on a holistic diagnosis of initial, process, and end visits. Patient Mr. I, 85 years old, complained of pain in the joints of the fingers of his right hand since 7 days ago. The patient has had these complaints since ± 20 years ago. Clinically the patient was diagnosed with Gout Arthritis (ICD-X M10.0). Furthermore, holistic management is carried out, namely intervention using poster media. In the evaluation, the results were obtained in the form of a better understanding of the disease and changes in behavior that have an impact on the success of therapy. The diagnosis and management of these patients has been carried out holistically, patient centered, family approach and community oriented based. In the process of behavior change, the patient has reached the trial stage.